Simple Kit to Facilitate Inorganic Ion Identification in Chemistry Learning - Laila Arifah; Leny Heliawati; Anna Permanasari (UIN Fatmawati Sukarno Bengkulu, 2025)
This study aims to develop a simple kit for identifying inorganic ions in chemistry education at the school level. The kit is designed to enhance the learning process by utilizing simple, safe materials that can be easily applied in school laboratories. This research employs a development approach using the ADDIE model (Analysis, Design, Development, Implementation, Evaluation), chosen for its effectiveness in designing, developing, and evaluating the feasibility of the kit.The dependent variables of this research include content feasibility, tool design, and safety levels in the context of educational use. The results show that the developed kit meets high standards of feasibility. Validation by subject matter experts revealed a content feasibility of 91.67%, while media experts rated the design and functionality at 94.50%. Additionally, laboratory safety experts confirmed the kit's safety with a rating of 97.33%.Based on these evaluations, it can be concluded that the developed kit is both valid and suitable for use in high school chemistry education. This kit is expected to improve student engagement and deepen their understanding of inorganic chemistry concepts.